THE POLITICAL CONSTRUCTIONS OF JUSTICE: REVIEWING ANTJIE KROG’S COUNTRY OF MY SKULL AND THE APPLICATION OF AFRICAN JURISPRUDENCE (The Pretoria Student Law Review, 2021)
This research aims to prove that politics shapes the law and, as such, can act as a catalyst to shape the law in accordance with African jurisprudence and Ubuntu. I structure my approach by explaining the difference between general and restricted jurisprudence and their foundations with the natural and positive law, respectively. In addition, I attempt to show that law and politics are inherently interrelated and should be viewed through a general jurisprudential perspective. I will further elaborate on the character played by politics on the South African law, both pre-1994 and in the postapartheid era. I direct my literature review to Antjie Krog’s Country of my skull. Krog’s account of the Truth and Reconciliation Commission (hereinafter referred to as the TRC) provides a platform for observation and analysis of the influence politics exerted on the law (and law enforcement) during apartheid. Krog’s account of the TRC also acts as a grounding for emphasising the particular African jurisprudence portrayed by the TRC itself and, finally, showing that a political atmosphere which incorporates African jurisprudence and Ubuntu into its political agenda will allow for the reflection of such a jurisprudence in the legal sphere. Krog’s illustration of the political shaping of the law creates a clear perspective of the influence of politics over the law. Furthermore, in attempting to illustrate this inherent power politics holds, particularly focusing on apartheid policies shaping the law (pre-1994), I too aim to show the power that politics can still play in shaping the law today, in accordance with African philosophy.